ANALISIS JARINGAN KOMUNIKASI ISU ‘REFORMASI’ DAN ‘TRANSFORMASI’ POLISI REPUBLIK INDONESIA DI MEDIA SOSIAL X (TWITTER) - Maylina Widya P. K; Irwan Dwi Arianto (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The violent phenomenon of police officials handling the demonstrations of August 2025 led to polri reform claims on social media x, which was then revitalized by police institutions through the polri transformation narrative. The research aims to analyze the differences in communications network structures and also in the reforming and transforming containers of polri in digital political communication. Research USES the mixed analysis approach, which is a quantitative analysis based on social network analysis (sna) and qualitative analysis using foucauldian accuracy analysis (fda). Data obtained from conversations on social media x during the 25th of August, 2025 and analyzed using nodexl software. Research shows that communication networks consist of 1,179 actors, 800 connections, 238 clusters, and a density value of 0.00146 that indicates a communications network is small. The polri reform discourse developed as an advocation-dominated communication between users through repeated, reply, and retweets to forma more participative public discussion space. Instead, polri transformation discourses are dominated by one-direction communication from institutional accounts with high levels of self-loops and thus relatively low interplay between users. Fda analysis shows that the two issues representing the containers between the people narrative and the institution narrative for establishing legitimacy. The polri reform narrative gains legitimacy through the collective experiences of people and the cases involving police, while the polri transformation narrative has not been fully accepted because it is being speculated has not reflected a real change. Research findings confirm that power in digital political communication is determined not only by the institutional authorities, but also by the legitimacy of discourses built through public participation in communication networks.